Blast-Induced Cholesteatomas After Spontaneous Tympanic Membrane Healing. (December 2019) - Ungar, Omer J.; Shilo, Shahaf; Anat, Wengier; Cavel, Oren; Handzel, Ophir; Oron, Yahav
Objectives: To characterize blast-induced cholesteatomas (BIC) in terms of symptoms, presentation, and location within the middle ear cleft (MEC). Design: A search for all English language articles in "MEDLINE" via "PubMed" and "Google Scholar" was conducted. Results: A total of 67 ears with BIC were included. Fifty-eight ears in which the traumatic perforation failed to spontaneously close were excluded, leaving seven case reports (eight patients, nine ears) for statistical analysis. Time between blast exposure to spontaneous tympanic membrane (TM) closure was 16 days to 10 months. Time between blast exposure and cholesteatoma diagnosis was 5 months to 4 years. The cholesteatomas were diagnosed due to symptoms in two ears, as asymptomatic finding on physical examination in one ear and as asymptomatic finding in axial imaging in three ears. Conclusions: BICs can develop behind intact tympanic membrane or along with TM perforation. Based on the current review, when a TM perforation and spontaneous healing were documented, after blast exposure, MRI scan is an integral component of the follow-up. The optimal timing for MRI performance after blast exposure, is yet to be identified.